Energy market liberalization for unlocking community-based green finance - Aki Suwa; Magali Dreyfus (Asian Development Bank Institute (ADBI), 2018)
There are increasing expectations of community-based financing for local renewable projects in Japan and in France: In both France and Japan, it has been about 10-20 years since the power market has been open to competition, where France is ahead, having fully liberalized its market to households in 2007, compared with that of Japan in 2016. With this as a background, a number of local governments are now able to establish power producer suppliers (PPS) to develop and supply renewable energy. Local renewable projects of the PPS, if properly designed, can function as a mechanism to create circular financial flow, where profits associated with electricity sales and the associated financial benefits may stay in the communities to form a shared stock for residential benefits. This paper illustrates cases in Japan and France, where both electricity markets were once centralized but are now open to new entrants, to identify if and how the projects have come about, and what the key factors are of creating community benefits. It also analyzes financial and credibility barriers through the case studies, to draw lessons for further community renewable development. The findings will help to understand the importance of community financial flow for community sustainability, and how the communities gained access to finance and investment.
Keywords: Q20; H23; R51; 330; power producer and suppliers; community energy; renewable energy; value added; hometown investment trust funds